A phase II study of S-1 and cisplatin with concurrent thoracic radiotherapy followed by durvalumab for unresectable, locally advanced non-small-cell lung cancer in Japan (SAMURAI study). (February 2021) - Tanzawa, Shigeru; Ushijima, Sunao; Shibata, Kazuhiko; Shibayama, Takuo; Bessho, Akihiro; Kaira, Kyoichi; Misumi, Toshihiro; Shiraishi, Kenshiro; Matsutani, Noriyuki; Tanaka, Hisashi; Inaba, Megumi; Haruyama, Terunobu; et al.
Background: Based on the results of the PACIFIC study, chemoradiotherapy followed by 1-year consolidation therapy with durvalumab was established as the standard of care for unresectable, locally advanced non-small-cell lung cancer (LA-NSCLC). However, some topics not foreseen in that design can be explored, including progression-free survival (PFS) and overall survival (OS) after the start of chemoradiotherapy, the proportion of patients who proceeded to consolidation therapy with durvalumab, and the optimal chemotherapeutic regimens. In Japan, the combination regimen of S-1 + cisplatin (SP), for which the results of multiple clinical studies have suggested a good balance of efficacy and tolerability, is frequently selected in clinical settings. However, the efficacy and safety of consolidation therapy with durvalumab following this SP regimen have not been evaluated. We therefore planned a multicenter, prospective, single-arm, phase II study. Methods: In treatment-naïve LA-NSCLC, two cycles of combination chemotherapy with S-1 (80–120 mg/body, Days 1–14) + cisplatin (60 mg/m 2, Day 1) will be administered at an interval of 4 weeks, with concurrent thoracic radiotherapy (60 Gy). Responders will then receive durvalumab every 2 weeks for up to 1 year. The primary endpoint is 1-year PFS rate. Discussion: Compared with the conventional standard regimen in Japan, the SP regimen is expected to be associated with lower incidences of pneumonitis, esophagitis, and febrile neutropenia, which complicate the initiation of consolidation therapy with durvalumab, and have higher antitumor efficacy during chemoradiotherapy. Therefore, SP-based chemoradiotherapy is expected to be successfully followed by consolidation therapy with durvalumab in more patients, resulting in prolonged PFS and OS. Toxicity and efficacy results of the SP regimen in this study will also provide information important to the future establishment of the concurrent combination of chemoradiotherapy and durvalumab. Trial registration: Japan Registry of Clinical Trials, jRCTs031190127, registered 1 November 2019, https://jrct.niph.go.jp/latest-detail/jRCTs031190127